2023
DOI: 10.1021/acs.langmuir.2c01691
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Control of Coffee Ring Formation in Carbon Nanotube Suspensions

Abstract: The coffee ring effect regularly occurs during the evaporation of colloidal droplets and is often undesirable. Here we show that adding a specific concentration of a surfactant can mitigate this effect. We have conducted experiments on aqueous suspensions of carbon nanotubes that were prepared with cationic surfactant dodecyltrimethylammonium bromide added at 0.2, 0.5, 1, 2, 5, and 10 times the critical micelle concentration. Colloidal droplets were deposited on candidate substrates for printed electronics wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…The average thickness was ≈393 nm, whereas the edge of the film was much thicker (≈999 nm). In earlier studies, the CNTs in the dispersions were observed to flow and accumulate along the droplet's edge due to the coffee ring effect [ 15 , 33 34 ]. As a result, the volume fraction of DWCNTs at the edge increased.…”
Section: Resultsmentioning
confidence: 99%
“…The average thickness was ≈393 nm, whereas the edge of the film was much thicker (≈999 nm). In earlier studies, the CNTs in the dispersions were observed to flow and accumulate along the droplet's edge due to the coffee ring effect [ 15 , 33 34 ]. As a result, the volume fraction of DWCNTs at the edge increased.…”
Section: Resultsmentioning
confidence: 99%
“…2008; Howard et al. 2023) and may further be enhanced by solute aggregation near the edge of the droplet (Orejon, Sefiane & Shanahan 2011; Weon & Je 2013; Larson 2014). However, at late stages of the evaporation, the contact line may depin and become mobile, moving inwards towards the droplet centre.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Throughout, we have assumed that the contact line remains pinned as the droplet evaporates. This has been shown to be a reasonable assumption for many configurations (see, for example, the experiments in Deegan et al 2000;Kajiya et al 2008;Howard et al 2023) and may further be enhanced by solute aggregation near the edge of the droplet (Orejon, Sefiane & Shanahan 2011;Weon & Je 2013;Larson 2014). However, at late stages of the evaporation, the contact line may depin and become mobile, moving inwards towards the droplet centre.…”
Section: Properties Of the Secondary Peakmentioning
confidence: 91%
See 1 more Smart Citation
“…At the same time, the “coffee ring” formation has also several disadvantages, such as the formation of nonuniform coating/patterning, formation of trench-like and raised ridge structures during three-dimensional (3D) printing with metal nanoparticle ink, , etc. As a result, there has been extensive research in developing strategies for arresting the coffee ring formation and ensuring a uniform and homogeneous deposition, which is critical for ensuring uniformity in various coating and patterning applications. , Some of the approaches for preventing the coffee ring formation involve the use of much smaller (nanoscopic) particles and ellipsoidal and flake-like particles, , performing the evaporation on oil-wetted surfaces, increasing the hydrophobicity (by physical and chemical modifications) of the surfaces on which the drop rests, application of an external electric field and acoustic waves during evaporation, controlling the interactions between the depositing particles and the solid substrate, use of surfactants, , and many more.…”
Section: Introductionmentioning
confidence: 99%